Penyelenggaraan Pelindungan Data Pribadi oleh Notaris berdasarkan Undang-Undang Nomor 27 Tahun 2022 tentang Pelindungan Data Pribadi - Mipon, Intan Permata; Putra, Mohamad Fajri Mekka (Jurnal Hukum & Pembangunan, 2023)
The endorsement of the Personal Data Protection Law (“UU PDP”) is aimed to providing legal certainty regarding protection for Indonesian citizens against various types of digital crimes. Therefore, entities processing personal data must adhere to the rules and principles stipulated in the UU PDP. In line with this, a Notary in the execution of their services is not exempt from storing and processing their clients personal data to be included in Notarial deed. Hence, under the Notary Profession Law, a Notary has the obligation to maintain the confidentiality of their profession while carrying out their duties. This raises the question addressed in this article : whether in the provision of their services, notaries are also subject to the UU PDP and what forms of protection they must implement in accordance with the regulations of the UU PDP. This article utilizes normative research that examines the application of norms within positive law, specifically Law Number 27 of 2022 regarding Personal Data Protection.